2004
DOI: 10.1068/p5004
|View full text |Cite
|
Sign up to set email alerts
|

Bistability and Biasing Effects in the Perception of Ambiguous Point-Light Walkers

Abstract: The perceptually bistable character of point-light walkers has been examined in three experiments. A point-light figure without explicit depth cues constitutes a perfectly ambiguous stimulus: from all viewpoints, multiple interpretations are possible concerning the depth orientation of the figure. In the first experiment, it is shown that non-lateral views of the walker are indeed interpreted in two orientations, either as facing towards the viewer or as facing away from the viewer, but that the interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
88
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 44 publications
10
88
3
Order By: Relevance
“…Brooks et al (2008) found a strong effect of figure gender on perceived in-depth orientation. Consistent with Vanrie et al (2004), male point-light walkers elicited a strong facing bias. However, the more strongly the figure was perceived as female, the more strongly it was perceived as facing away from the viewer.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Brooks et al (2008) found a strong effect of figure gender on perceived in-depth orientation. Consistent with Vanrie et al (2004), male point-light walkers elicited a strong facing bias. However, the more strongly the figure was perceived as female, the more strongly it was perceived as facing away from the viewer.…”
Section: Introductionsupporting
confidence: 52%
“…One could assume, for instance, that in daily life, observers are more often confronted with a person facing toward them than with a person that is oriented away. There are, however, no natural image statistics available that show that this is indeed the case (Vanrie et al, 2004). Otherwise, it could be hypothesized that a person who is facing toward an observer is more socially or behaviorally relevant for the observer than a person who is oriented away.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet observers show a bias toward seeing a walker facing the viewer (Vanrie, Dekeyser, & Verfaillie, 2004). Recently, we reported that this facing bias strongly depends on the gender of the walker (Brooks et al, 2008).…”
mentioning
confidence: 99%
“…Since then, it has been reported that humans are able to extract a variety of behaviorally relevant characteristics, including the type of action (Dittrich, 1993;, the identity of the actor Loula, Prasad, Harber, & Shiffrar, 2005), and the actor's gender Pollick, Kay, Heim, & Stringer, 2005;Troje, 2002), emotional state (Dittrich, Troscianko, Lea, & Morgan, 1996;Montepare, Goldstein, & Clausen, 1987), and age (Montepare & Zebrowitz-McArthur, 1988). Only more recently, however, has the question of how observers interpret the in-depth orientation of point-light figures systematically been addressed (Jackson, Cummins, & Brady, 2008;Vanrie, Dekeyser, & Verfaillie, 2004;Vanrie & Verfaillie, 2006, 2008.…”
mentioning
confidence: 99%